2011
DOI: 10.4314/jafs.v9i2.1
|View full text |Cite
|
Sign up to set email alerts
|

Application of the Stochastic Production Frontier to the Measurement of Technical Efficiency of Fish Farming in Umuahia Metropolis, Abia State, Nigeria

Abstract: The study examined the factors that affect fish production among fish farmers who use pond for their fish production in Umuahia Metropolis, Abia State. Thirty six respondents were sampled from a list of fish farmers derived from Abia State Agricultural Development Programme Office. The Cob Douglas stochastic production function was used to determine factors that affect fish production as well as the factors that affect the technical efficiency of fish production. Pond size (p=0.05), capital input (p=0.01), lab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
2
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 3 publications
1
2
0
Order By: Relevance
“…Indicatively, consumers shift their preference towards fish or egg with increase in age as it is always recommended for the aged due to its content. This result agrees with the findings of Igwe and Onyekwere (2007) and Sharu (2000) on their work on meat demand in Umuahia and Sokoto Metropolis of Nigeria, respectively.…”
Section: Results and Discussion Effect Of Socio-economic Characterist...supporting
confidence: 92%
“…Indicatively, consumers shift their preference towards fish or egg with increase in age as it is always recommended for the aged due to its content. This result agrees with the findings of Igwe and Onyekwere (2007) and Sharu (2000) on their work on meat demand in Umuahia and Sokoto Metropolis of Nigeria, respectively.…”
Section: Results and Discussion Effect Of Socio-economic Characterist...supporting
confidence: 92%
“…The literature review identified only a small number of studies that examined Nigerian consumers' demand for meat products; however, none used nationally representative country samples, and most used small cross-sectional samples (Igwe and Onyekwere 2007; 2 Gibson and Kim (2011) can also be seen both as a comparison of demand estimation results using different datasets and an assessment of econometric procedures used to account for infrequency of purchases. Alimi 2013;Ogundari 2012).…”
Section: Literature Reviewmentioning
confidence: 99%
“…These non-conventional adsorbents include bacterial, algal, and fungal biomass. [44][45][46][47][48] Other lowcost adsorbents have been prepared from sunflower stalks, [49] maize cob and husk, [50][51][52] shea butter seed husk, [53,54] cassava waste, [55] white star apple, [56] saw dust-carbon, [57] sago waste, [58] rice husk, [59,60] peanut hull, [61] walnut, [62] lignite, [63] sugarcane bagasse cellulose, [64] sheep bone, [65] and many others.…”
Section: Purification Of Mercury-containing Wastewater Using Low-costmentioning
confidence: 99%